Dissolved organic matter photodegradation in a water supply reservoir on temperate oceanic climate (Cfb): a case study of Passaúna reservoir, Brazil - Carolina Ferreira de Souza; Heloise Garcia Knapik; Júlio César Rodrigues de Azevedo (Revista Brasileira de Recursos Hídricos, 2022)
Abstract Photodegradation is an important process for aquatic metabolism, related to the dissolved organic matter (DOM) transformation in water. For example, in a water supply reservoir, DOM is an important parameter since it can react and form disinfection by-products during water treatment. Thus, the understanding and determination of photodegradation rates are especially relevant for water resources management since they can influence DOM transformation in the water column. However, besides its relevance, few studies were conducted in the southern hemisphere for photodegradation rates determination. Therefore, we carried out field experiments to characterize and evaluate DOM photodegradation rate ‒ at different depths and in two solar irradiation periods ‒ through the application of absorption spectroscopy techniques in the UV-Vis region and fluorescence excitation-emission matrices (EEM) combined with the dissolved organic carbon (DOC) measurement. Low concentrations of natural DOM and nutrients in the aquatic environment were measured during the field monitoring. Our results indicate that photodegradation rates for a temperate oceanic climate reservoir were proportional to the availability of solar radiation, being more representative considering the time scale.